Data-driven prioritisation framework for micropollutants in tropical estuaries: Unveiling hidden toxicity and deterministic health risks - Shengkai Cao; Weichen Zhao; Yintian Zhang; Xiaodi Zhang; Songyue Yang; Haofei Lu; Tongyu Guo; Meiyan Hu; Jingyi Xie; Xiaohui Wang; Guangshui Na (Environmental Pollution, 2026)

Deciphering the long-term performance and underlying mechanisms of an engineering-scale anaerobic-anoxic-oxic-anaerobic-vibrating MBR process - Shujuan Che; Weichen Lin; Haojie Ding; Congcong Zhang; Xiangyu Li; Kaichang Yu; Huanhuan Guan; Jie Shi; Yun Yang; Xia Huang (ENGINEERING Environment, 2026)

Health insurance coverage and health-related Sustainable Development Goal indicators in 62 low- and middle-income countries: a household fixed-effects analysis - Simiao Chen; Kaiyuan Min; Qiushi Chen; Lirui Jiao; Pascal Geldsetzer; Ting Yang; Ke Huang; Hongtao Niu; Weichen Wang; Mosa Moshabela; Rifat Atun; De-Pei Liu; et al. (Science Bulletin, 2026)

Non-monotonic evolution of reservoir permeability during water flooding: Impact of development history of depleted hydrocarbon reservoirs on hydrogen recovery efficiency - Xufeng Liang; Yongfei Yang; Tonghui Liu; Ruixu Wan; Haoyun Li; Qi Zhang; Weichen Sun; Yingwen Li; Hai Sun; Lei Zhang; Junjie Zhong; Kai Zhang; et al. (Gas Science and Engineering, 2026)

FengYuan: An End-to-End Global Weather Forecasting Model Driven by Multi-Source Observational Data - Zhaoming Liang; Yang Li; Yaqiang Wang; Yiheng Shi; Junming Chen; Fenghua Ling; Enda Zhu; Hai Wang; Lei Bai; Huabing Ke; Zhongyan Hu; Xiaoxu Liu; et al. (Journal of Meteorological Research, 2026)

Rotor tilt effect on the wake of tandem offshore wind turbines via large-eddy simulation - Weichen Wang; Ai Wang; Sherif H. Alhosary; Junwei Yang; Hua Yang (Ocean Engineering, 2026)

Improving watershed-scale daily nutrient simulation using a process-model-informed graph attention network with multi-source data integration - Weichen Wang; Guowangchen Liu; Mingjing Wang; Yan Pan; Yukun Ma; Lu Yang; Jing Sang; Zhenyao Shen; Lei Chen (Water Research, 2026)

Multiscale damage mechanisms of reservoir bank sandstone under prolonged immersion in pumped-storage hydropower projects: From microscale processes to macroscopic fracture - Hexing Zhang; Qiang Xie; Jiwei Jia; Kunpeng Lu; Fubo Yang; Weichen Sun (Engineering Geology, 2026)

Accurate and real-time fish feeding intensity scoring using channel convolution GLU and SMFA attention fusion in recirculating aquaculture system - Chenjian Liu; Xinting Yang; Baoliang Liu; Zhenxi Zhao; Pingchuan Ma; Tingting Fu; Weichen Hu; Xiaoqiang Gao; Chao Zhou (Aquaculture, 2026)

Video and six-axis inertial sensor signals fusion for fish feeding behavior recognition in recirculating aquaculture system - Pingchuan Ma; Zhenxi Zhao; Xinting Yang; Tingting Fu; Weichen Hu; Chao Zhou (Aquacultural Engineering, 2026)

Covalent organic cage with boosting stability and biosafety for integrated platform: MRI mediated chem/photodynamic therapy - Xin Linghu; Wei He; Kangkang Huang; Weichen Li; Hong Yang; Shiping Yang; Jingjing Jiao (Chemical Engineering Journal, 2025)

Reduction of antibiotics and antibiotic resistance genes in simulated-sunlight-supported counter-diffusion bacteria-Algae biofilms: Interface properties and functional gene responses - Han Zhang; Jiao Yin; Haotian Jiang; Weichen Zeng; Yufei Cheng; Jiaxuan Yang; Dachao Lin; Langming Bai; Heng Liang (Water Research, 2025)

Soundscape diversity in urban green spaces: Spatial-temporal variations, influencing factors and optimization strategies - Yi Xiang; Qi Meng; Mengmeng Li; Da Yang; Weichen Zhang (Urban Forestry & Urban Greening, 2025)

Enantioselective toxicological effects of chiral profenofos and 2-Bromo-4-chlorophenol on bovine serum albumin: Molecular-cellular-biological multilevel evaluation - Wenze Li; Weichen You; Xiaofan Yang; Yi Wang; Rimao Hua; Saraschandra Naraginti; Meiqing Zhu (Food Chemistry, 2025)

The trade-off between the removal efficiency and by-products formation for isoquinoline removal in coking wastewater by UV-based AOPs - Xiaomeng Zhang; Shuai Tian; Hongjin Wu; Weichen Yang; Jingwei Guo; Shibo Zhang; Juan Dang; Qingzhu Zhang (Chemical Engineering Journal, 2025)

Association Between Primary Dysmenorrhea and Mental Health Traits: A Study Based on Multi-Phenotype Correlation Network and Mendelian Randomization Analysis in Female College Students - Huiting Jiangzhou; Hanpeng Xu; Yanqin Wen; Zeyi Guan; Yang Zheng; Xuemin Jian; Weichen Song; Aamir Fahira; Jinmai Zhang; Qing Zhang; Ying Zhao; Manfei Zhang; et al. (Phenomics, 2025)

Investigating the mechanism of Fuling-Banxia-Dafupi in the treatment of diabetic kidney disease using network pharmacology and molecular docking - Qi Wang; Yiran Pang; Han Yang; Xin Zhang; Weichen Nie; Jiahui Zhou; Rui Chen (Natural Product Research, 2025)

Semi-supervised fish school density estimation and counting network in recirculating aquaculture systems based on adaptive density proxy - Kaijie Zhu; Xinting Yang; Caiwei Yang; Tingting Fu; Pingchuan Ma; Weichen Hu; Chao Zhou (Computers and Electronics in Agriculture, 2025)

DCA-MVIT: Fused DSGated convolution and CA attention for fish feeding behavior recognition in recirculating aquaculture systems - Weichen Hu; Xinting Yang; Pingchuan Ma; Tingting Fu; Chao Zhou (Aquaculture, 2025)

High energy storage density achieved in polymer composites by hierarchical interface engineering design - Yang Liu; Jin Qian; Yan Guo; Weichen Zhao; Tiezhu Guo; Diming Xu; Zhentao Wang; Guoqiang He; Jiwei Zhai; Yao Zhou; Wenfeng Liu; Di Zhou (Chemical Engineering Journal, 2025)

Modeling regional private income and its embedded carbon emissions: sources, flows and inequalities - Runchuan Feng; Junnian Song; Qilin Cao; Heran Zheng; Weichen Zhong; Wei Yang (Science of The Total Environment, 2025)

Metabolic and protein expression responses of Shewanella baltica in golden pomfret broths to slightly acidic electrolysed water - Xiaowei Lou; Weichen Shu; Loo Chien Wang; Yan Ting Lim; Tianyun Zhao; Hang Liu; Radoslaw M. Sobota; Hongshun Yang (Food Chemistry, 2025)

DF-DETR: Dead fish-detection transformer in recirculating aquaculture system - Tingting FU; Dejun Feng; Pingchuan Ma; Weichen Hu; Xinting Yang; Shantan Li; Chao Zhou (Aquaculture International, 2025)

Nondestructive perch target detection and size measurement from RGB-D images in recirculating aquaculture system - Weichen Hu; Xinting Yang; Pingchuan Ma; Kaijie Zhu; Tingting Fu; Chao Zhou (Aquaculture International, 2025)

Fish feeding behavior recognition using time-domain and frequency-domain signals fusion from six-axis inertial sensors - Pingchuan Ma; Xinting Yang; Weichen Hu; Tingting Fu; Chao Zhou (Computers and Electronics in Agriculture, 2024)

Insights into the azo dye decolourisation and denitrogenation in micro-electrolysis enhanced counter-diffusion biofilm system - Tianyi Wang; Xiaohang Han; Yufei Cheng; Jiaxuan Yang; Langming Bai; Weichen Zeng; Hesong Wang; Nuo Cheng; Han Zhang; Guibai Li; Heng Liang (Bioresource Technology, 2024)

Theoretical insight into the removal process of isoquinoline by UV/Cl and UV/PDS: Oxidation mechanism and toxicity assessment - Xiaomeng Zhang; Hongjin Wu; Jingwei Guo; Weichen Yang; Yongchun Zhao; Juan Dang; Shibo Zhang; Qingzhu Zhang; Wenxing Wang (Chemosphere, 2024)

In situ electron generation through Fe/C supported sludge coupled with a counter-diffusion biofilm for electron-deficient wastewater treatment: Binding properties and catalytic competition mechanism of nitrate reductase - Han Zhang; Yufei Cheng; Linhong Qiu; Weichen Zeng; Tianyi Hu; Jiaxuan Yang; Jinlong Wang; Hesong Wang; Weijia Gong; Heng Liang (Water Research, 2024)

A low-fouling electrochemical biosensor based on BSA hydrogel doped with carbon black for the detection of cortisol in human serum - Xiaohang Yu; Weichen Meng; Yang Li; Xiliang Luo (Analytica Chimica Acta, 2024)

Hydrogenation of waste PET degraded bis(2-hydroxyethyl)cyclohexane- 1,4-dicarboxylate to 1,4-cyclohexanedimethanol over Cu-based catalysts - Xinlin Jiang; Zhili Chang; Lei Yang; Weichen Du; Zhaoyin Hou (Fuel, 2024)

Arsenic pollution concerning surface water and sediment of Jie River: A pilot area where gold smelting enterprises are concentrated - Yan Jin; Weichen Zhu; Jia Li; Dayong Cui; Zhibin Zhang; Guoxin Sun; Yongguan Zhu; Huanhuan Yang; Xu Zhang (Environmental Research, 2024)

Cryogenian and Ediacaran integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Lang Sun; Malik Muhammad Saud Sajid Khan; Chuan Yang; Zhixin Sun; Bing Pan; Shehryar Ahmed; Lanyun Miao; Weichen Sun; Chunlin Hu; Xiaojuan Sun; Cui Luo; Bo Chen; et al. (Science China Earth Sciences, 2024)

FCFormer: fish density estimation and counting in recirculating aquaculture system - Kaijie Zhu; Xinting Yang; Caiwei Yang; Tingting Fu; Pingchuan Ma; Weichen Hu (Frontiers in Marine Science, 2024)
In intelligent feeding recirculating aquaculture system, accurately estimating fish population and density is pivotal for management practices and survival rate assessments. However, challenges arise due to mutual occlusion among fish, rapid movement, and complex breeding environments. Traditional object detection methods based on convolutional neural networks (CNN) often fall short in fully addressing the detection demands for fish schools, especially for distant and small targets. In this regard, we introduce a detection framework dubbed FCFormer (Fish Count Transformer). Specifically, the Twins-SVT backbone network is employed first to extract global features of fish schools. To further enhance feature extraction, especially in the fusion of features at different levels, a Bi-FPN aggregation network model with a CAM Count module is incorporated (BiCC). The CAM module aids in focusing more on critical region features, thus rendering feature fusion more cohesive and effective. Furthermore, to precisely predict density maps and elevate the accuracy of fish counting, we devised an adaptive feature fusion regression head: CRMHead. This approach not only optimizes the feature fusion process but also ensures superior counting precision. Experimental results shown that the proposed FCFormer network achieves an accuracy of 97.06%, with a mean absolute error (MAE) of 6.37 and a root mean square error (MSE) of 8.69. Compared to the Twins transformer, there's a 2.02% improvement, outperforming other transformer-based architectures like CCTrans and DM_Count. The presented FCFormer algorithm can be effectively applied to fish density detection in intelligent feeding recirculating aquaculture system, offering valuable input for the development of intelligent breeding management systems.

Effect of slightly acidic electrolysed water against Shewanella baltica in phosphate-buffered saline and on golden pomfret sticks - Xiaowei Lou; Weichen Shu; Yue Wang; Chenxi Guo; Hang Liu; Hongshun Yang (Food Control, 2024)

Substituting readily available nitrogen fertilizer with controlled-release nitrogen fertilizer improves crop yield and nitrogen uptake while mitigating environmental risks: A global meta-analysis - Yajun Zhang; Weichen Ren; Kuanyu Zhu; Jiangyao Fu; Weilu Wang; Zhiqin Wang; Junfei Gu; Jianchang Yang (Field Crops Research, 2024)

Carbon-negative heat-stored limestone calcined clay cement mortar containing form-stable phase change materials - Kunyang Yu; Chengcong Liu; Liang Li; Weichen Tian; Yingzi Yang; Yushi Liu (Journal of Cleaner Production, 2024)

Study of cone penetration test in granular soil considering realistic particle shapes by discrete element method in 3D - Kai Wu; Weichen Sun; Songyu Liu; Dayu Yang (European Journal of Environmental and Civil Engineering, 2023)

Preparation of magnesium potassium phosphate cement from municipal solid waste incineration fly ash and lead slag co-blended: Ca-induced crystal reconstruction process and Pb-Cl synergistic solidification mechanism - Shiwei Liu; Xing Cao; Weichen Yang; Runjie Liu; Lin Fang; Rui Ma; Juan Peng; Shuaifei Zheng; Fei Ji (Journal of Hazardous Materials, 2023)

The evolution of the relationship among stakeholders in port integration: Evidence from tripartite evolutionary game analysis - Weichen Gao; Weiyou Guo; Shuang Zhou; Shanhua Wu; Zhongzhen Yang (Ocean & Coastal Management, 2023)

The microalgae-based wastewater treatment system coupled with Cerium: A potential way for energy saving and microalgae boost - Wei Zuo; Zhiwei Chen; Jun Zhang; Wei Zhan; Huili Yang; Lipin Li; Weichen Zhu; Yuqing Mao (Environmental Science and Pollution Research, 2023)

Changes in texture, rheology and volatile compounds of golden pomfret sticks inoculated with Shewanella baltica during spoilage - Xiaowei Lou; Xiaokang Wen; Leijian Chen; Weichen Shu; Yue Wang; Tung Thanh Hoang; Hongshun Yang (Food Chemistry, 2023)

Lead-chlorine synergistic immobilization mechanism in municipal solid waste incineration fly ash (MSWIFA)-based magnesium potassium phosphate cement - Xing Cao; Qiushi Zhang; Weichen Yang; Lin Fang; Shiwei Liu; Rui Ma; Kai Guo; Ning Ma (Journal of Hazardous Materials, 2023)

Investigating the effects of environment, corrosion degree, and distribution of corrosive microbial communities on service-life of refined oil pipelines - Zhengquan Wang; Yantao Li; Jie Ren; Weichen Xu; Lihui Yang (Environmental Science and Pollution Research, 2022)

Research status and development trends in the field of marine environment corrosion: a new perspective - Zhengquan Wang; ZiYang Zhou; Weichen Xu; Dan Yang; Yong Xu; Lihui Yang; Jie Ren; Yantao Li; Yanliang Huang (Environmental Science and Pollution Research, 2021)

Corrosion behavior of Q235B carbon steel in simulated seawater pumped storage system under operational conditions - Dan Yang; Yanliang Huang; Jianqiu Li; Yanming Gao; Xia Zhao; Weichen Xu (Journal of Oceanology and Limnology, 2020)

Dominant modes of CMIP3/5 models simulating northwest Pacific circulation anomalies during post-ENSO summer and their SST dependence - Weichen Tao; Gang Huang; Pengfei Wang; Yang Liu; Guanhuan Wen; Danhong Dong (Theoretical and Applied Climatology, 2019)

Mutations in human IFT140 cause non-syndromic retinal degeneration - Mingchu Xu; Lizhu Yang; Feng Wang; Huajin Li; Xia Wang; Weichen Wang; Zhongqi Ge; Keqing Wang; Li Zhao; Hui Li; Yumei Li; Ruifang Sui; et al. (Human Genetics, 2015)